A Systematic Literature Review on the Use of Digital Books in Science Learning in the Society 5.0 Era - Zikra, Zikra; Safitri, Elza; Yerimadesi, Yerimadesi; Yohandri, Yohandri; Fadilah, Muhyiatul (Biosfer: Jurnal Tadris Biologi, 2026)
This study examines the use of digital books in science learning within the context of Society 5.0 through a Systematic Literature Review (SLR). The review followed the PRISMA 2020 guidelines and analyzed 27 articles indexed in Scopus published between 2021 and 2025. The findings indicate that digital books contribute positively to students’ learning outcomes, critical thinking skills, motivation, and digital literacy. Interactive features such as multimedia integration, augmented reality, and AI-based feedback support more adaptive and contextual science learning. The review also identified four major research themes: digital book design and development, impact on learning outcomes, integration with Society 5.0 principles, and implementation challenges. Despite their benefits, several barriers remain, including limited digital infrastructure, unequal access to technology, and low teacher readiness in digital pedagogy. Overall, digital books have strong potential to support innovative and student-centered science learning aligned with the demands of Society 5.0. Sistematik Literatur Review Penggunaan Buku Digital dalam Pembelajaran Sains pada Era Society 5.0 ABSTRAK: Penelitian ini mengkaji penggunaan buku digital dalam pembelajaran sains pada konteks Society 5.0 melalui Systematic Literature Review (SLR). Kajian dilakukan mengikuti pedoman PRISMA 2020 dengan menganalisis 27 artikel terindeks Scopus yang diterbitkan pada tahun 2021–2025. Hasil penelitian menunjukkan bahwa buku digital memberikan kontribusi positif terhadap hasil belajar, kemampuan berpikir kritis, motivasi belajar, dan literasi digital siswa. Fitur interaktif seperti integrasi multimedia, augmented reality, dan umpan balik berbasis AI mendukung pembelajaran sains yang lebih adaptif dan kontekstual. Kajian ini juga mengidentifikasi empat tema utama penelitian, yaitu desain dan pengembangan buku digital, dampak terhadap hasil belajar, integrasi prinsip Society 5.0, serta tantangan implementasi. Meskipun memiliki banyak manfaat, penerapan buku digital masih menghadapi hambatan berupa keterbatasan infrastruktur digital, ketimpangan akses teknologi, dan rendahnya kesiapan guru dalam pedagogi digital. Secara keseluruhan, buku digital berpotensi mendukung pembelajaran sains yang inovatif dan berpusat pada siswa sesuai tuntutan Society 5.0.